Language Skills of Deaf Students Using The Computer Assisted Instruction (CAI) Application Program Model - Wagino, W.; Abidin, Zaenal; Ekasari, Diah; Pujiastuti, Asri; Sukartiningsih, Wahyu (International Journal of Language Education, 2025)
Language skills are crucial for deaf students as they facilitate communication, education, and social integration. Without adequate language proficiency, deaf students face difficulties in academic learning and personal development. This research explores how the Computer-Assisted Instruction (CAI) application model enhances the language skills of deaf students by integrating technology-based learning tools. The study employs a Research and Development (R&D) approach using the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation. The CAI model incorporates multimedia elements, including text, animations, videos, and interactive exercises, to enhance reading comprehension, writing abilities, and vocabulary acquisition. The program is designed using Macromedia Director and other supporting software to create an interactive learning environment tailored for deaf students. Findings indicate that the CAI model significantly improves reading comprehension, writing skills, and vocabulary retention. Students show increased motivation, engagement, and self-paced learning abilities. Teachers report improved student participation and communication through visual-based learning tools. However, challenges such as accessibility to digital resources and teacher training need to be addressed. The study highlights CAI’s effectiveness in promoting inclusive education for deaf students. Future research should explore AI-driven adaptive learning, gamification, and real-time speech-to-text translation to further enhance digital learning for deaf students. The integration of CAI in special education presents a transformative approach to improving language skills and educational outcomes for deaf learners.